Short tandem repeat polymorphism in the promoter region of cyclophilin 19B drives its transcriptional upregulation and contributes to drug resistance in the malaria parasite Plasmodium falciparum - Kucharski, Michal (2023)
Resistance of the human malaria parasites, Plasmodium falciparum, to artemisinins is now fully established in Southeast Asia and is gradually emerging in Sub-Saharan Africa. Although nonsynonymous SNPs in the pfk13 Kelch-repeat propeller (KREP) domain are clearly associated with artemisinin resistance, their functional relevance requires cooperation with other genetic factors/alterations of the P. falciparum genome, collectively referred to as genetic background. Here we provide experimental evidence that P. falciparum cyclophilin 19B (PfCYP19B) may represent one putative factor in this genetic background, contributing to artemisinin resistance via its increased expression. We show that overexpression of PfCYP19B in vitro drives limited but significant resistance to not only artemisinin but also piperaquine, an important partner drug in artemisinin-based combination therapies. We showed that PfCYP19B acts as a negative regulator of the integrated stress response (ISR) pathway by modulating levels of phosphorylated eIF2α (eIF2α-P). Curiously, artemisinin and piperaquine affect eIF2α-P in an inverse direction that in both cases can be modulated by PfCYP19B towards resistance. Here we also provide evidence that the upregulation of PfCYP19B in the drug-resistant parasites appears to be maintained by a short tandem repeat (SRT) sequence polymorphism in the gene's promoter region. These results support a model that artemisinin (and other drugs) resistance mechanisms are complex genetic traits being contributed to by altered expression of multiple genes driven by genetic polymorphism at their promoter regions.